Money Matters: From the Power of Capital to Political Power in the City of Tasikmalaya, Indonesia - Mohamad Ali Andrias; Leo Agustino; Muhammad Ashsubli; Dina Fitriani Wulandari (Journal of Government and Civil Society, 2026)
Since the 1998 Reformation, Indonesian politics has experienced major institutional transformation toward electoral democracy. One crucial change is the direct election of regional heads, including mayors, who were previously appointed by governors with central government approval. However, this shift also brings new challenges. This article examines the case of PT. Mayasari Bakti Utama (MBU) as an example of a capital-based political dynasty. The family owning this large transportation company has utilized its economic resources to build political power in Tasikmalaya, Indonesia. The study aims to explain how both informal actors (such as kyai) and formal actors (political party elites) are mobilized for family political interests. Using field observations, in-depth interviews, focus group discussions, and library research, this study finds that, first, the MBU family employs kyai networks to build legitimacy among Tasikmalaya's religious population. The charisma of the kyai shapes voter behavior in favor of the MBU family. Second, political elites use their positions to support the family's electoral ambitions. Third, unequal capital distribution enables the MBU family to "buy" influence and secure political power. Thus, economic capital strongly determines the political configuration in Tasikmalaya, reinforcing previous studies that political power in Indonesia often originates from economic strengthSejak Reformasi 1998, politik Indonesia telah mengalami transformasi institusional besar menuju demokrasi elektoral. Salah satu perubahan penting adalah pelaksanaan pemilihan kepala daerah secara langsung, termasuk pemilihan wali kota, yang sebelumnya diangkat oleh gubernur dengan persetujuan pemerintah pusat. Namun, perubahan ini juga membawa tantangan baru. Artikel ini mengkaji kasus PT. Mayasari Bakti Utama (MBU) sebagai contoh dinasti politik berbasis modal. Keluarga pemilik perusahaan transportasi besar ini memanfaatkan sumber daya ekonominya untuk membangun kekuatan politik di Tasikmalaya, Indonesia. Tujuan penelitian ini adalah menjelaskan bagaimana aktor informal (seperti kyai) dan aktor formal (seperti elit partai politik) dimobilisasi untuk kepentingan politik keluarga. Dengan menggunakan observasi lapangan, wawancara mendalam, diskusi kelompok terarah (FGD), dan studi pustaka, penelitian ini menemukan bahwa: pertama, keluarga MBU memanfaatkan jaringan kyai untuk membangun legitimasi di tengah masyarakat Tasikmalaya yang religius. Karisma kyai berpengaruh besar terhadap perilaku pemilih yang mendukung keluarga MBU. Kedua, elit politik menggunakan posisinya untuk mendukung ambisi elektoral keluarga tersebut. Ketiga, ketimpangan distribusi modal memungkinkan keluarga MBU untuk "membeli" pengaruh dan mengamankan kekuasaan politik. Dengan demikian, kekuatan ekonomi sangat menentukan konfigurasi politik di Tasikmalaya, sekaligus memperkuat temuan penelitian sebelumnya bahwa kekuasaan politik di Indonesia sering kali berakar dari kekuatan modal ekonomi.